1978
DOI: 10.1139/b78-124
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Fusarium graminearum by maize pollen

Abstract: Maize pollen stimulated infection of maize by Fusarium graminearum Schwabe both in in vivo and in vitro. Significant increases in percentage germination of macroconidia and length of germ tube of F. graminearum occurred in the presence of pollen dialysate, while dextrose and sucrose were not as stimulatory. All concentrations of macroconidia used to inoculate greenhouse-grown maize plants were equally effective in producing lesions in the leaf axils in the presence of pollen. Without pollen, only the highest i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1982
1982
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…The compounds responsible for this stimulatory activity were later identified as betaine and choline (Strange et al 1974). A similar response of F. graminearum to maize pollen was reported by Naik and Busch (1978), and Pugh et al (1933) also observed greater infection in the presence of anthers. In contrast, Engle et al (2002) did not observe significant stimulation of fungal growth in the presence of purified betaine or choline, nor in the presence of anther extracts.…”
Section: Germination and Initial Growth Of The Fungussupporting
confidence: 59%
“…The compounds responsible for this stimulatory activity were later identified as betaine and choline (Strange et al 1974). A similar response of F. graminearum to maize pollen was reported by Naik and Busch (1978), and Pugh et al (1933) also observed greater infection in the presence of anthers. In contrast, Engle et al (2002) did not observe significant stimulation of fungal growth in the presence of purified betaine or choline, nor in the presence of anther extracts.…”
Section: Germination and Initial Growth Of The Fungussupporting
confidence: 59%
“…4). The ability of compounds from maize pollen to stimulate the germination and growth of F. graminearum was demonstrated by Naik and Busch (1978), and the presence of pollen and (or) anthers has also been shown to stimulate growth of F. graminearum in wheat (Strange and Smith 1971;Miller et al 2004).…”
Section: In Vitro Experiments With Excised Earsmentioning
confidence: 99%
“…Much of the pollen shed from the tassels lodged in the axils of leaves subtending maturing cobs, and at tassel senescence many male flowers and other debris were trapped in this region. Naik & Busch (1978) reported that maize pollen stimulated infection of the leafaxils of maize plants by F. graminearum. Water was often seen trapped in the leafaxils and these regions have the potential to act as reservoirs of infection initially for the leaf, and later for the husk of the cob maturing in its axil.…”
Section: Leavesmentioning
confidence: 99%